Rola ojca w kontekście hospicyjnego wsparcia terminalnie chorego dziecka i jego rodziny - Godawa, Grzegorz (Analecta Cracoviensia, 2012)
A child’s terminal illness makes it very difficult for the father to fulfil family functions. Hospice support provided by a multidisciplinary team aims at overcoming these difficulties. The mission of a hospice is to care for both the ill child and its family. The support offered to the father of the ill child is specific and adequate to the father’s social role. It embraces the basic spheres of the father’s activity in the family and is oriented to his needs.